Ultrafast Doppler reveals the mapping of cerebral vascular resistivity in neonates - Demené, Charlie (Nature Publishing Group, 2014)
In vivo mapping of the full vasculature dynamics based on Ultrafast Doppler is showed noninvasively in the challenging case of the neonatal brain. Contrary to conventional pulsed-wave (PW) Doppler Ultrasound limited for >40 years to the estimation of vascular indices at a single location, the ultrafast frame rate (5,000 Hz) obtained using plane-wave transmissions leads to simultaneous estimation of full Doppler spectra in all pixels of wide field-of-view images within a single cardiac cycle and high sensitivity Doppler imaging. Consequently, 2D quantitative maps of the cerebro-vascular resistivity index (RI) are processed and found in agreement with local measurements obtained on large arteries of healthy neonates using conventional PW Doppler. Changes in 2D resistivity maps are monitored during recovery after therapeutic whole-body cooling of full-term neonates treated for hypoxic ischemic encephalopathy. Arterial and venous vessels are unambiguously differentiated on the basis of their distinct hemodynamics. The high spatial (250 × 250 μm(2)) and temporal resolution (<1 ms) of Ultrafast Doppler imaging combined with deep tissue penetration enable precise quantitative mapping of deep brain vascular dynamics and RI, which is far beyond the capabilities of any other imaging modality.